Reengineering health care a manifesto for radically rethinking health care delivery - Champy, James 1942- (FT Press, 2010)
"Jim Champy and Dr. Harry Greenspun show how to apply the proven reengineering methodology in health care: throughout physician practices, hospitals, and even entire health systems. You'll meet innovative and visionary leaders who've been successfully reengineering organizations across the entire delivery spectrum and learn powerful lessons for improving quality, reducing costs, and expanding access. This book doesn't just demonstrate the immense potential of health care reengineering to revolutionize health care delivery: it offers a clear roadmap for realizing that potential in your own organization"--Resource description page
Includes index
Keywords: Health care reform -- United States; Health reformers -- United States; Medical care -- United States; Reengineering (Management); Organizational change; Medical policy; Organization; Medical care; Health planning; Health services administration; Health care reform; Social control; Social sciences; Sociology; Health Care Reform -- methods; Organizational Innovation; Health Policy; Organization and Administration; Delivery of Health Care; Health Planning; Health Care Reform; Social Control, Formal; Social Sciences; Patient Care; Services de santé; Réforme; États-Unis; Réingénierie organisationnelle; Politique sanitaire; Organisation; Prestation de soins; Santé publique; Planification; Services de santé; Administration; Services de santé; Réforme; Changement organisationnel; Contrôle social; Sciences sociales; Sociologie; Hygiénistes (Mouvement); États-Unis; Soins médicaux; social sciences; sociology; POLITICAL SCIENCE; Public Policy; Social Security; POLITICAL SCIENCE; Public Policy; Social Services & Welfare; Health reformers; Health care; organizational effectiveness; USA; United States